Wrist Ankle Acupuncture (WAA) and Body Acupuncture Accelerates Neurorehabilitation in Bell's Palsy: A Case Report - Rina Nurbani; Dwi Rachma Helianthi (Journal of Agromedicine and Medical Sciences, 2021)
Bell’s Palsy (BP) is an acute unilateral facial paralysis due to idiopathic inflammation of the peripheral facial nerve. Corticosteroids, antiviral drugs, and physical therapy could be useful to treat BP, however these treatments could not bring complete recovery. Acupuncture could be an alternative option for BP and to show its effectiveness, we present a case report, a patient with BP treated with acupuncture. A 48-year-old female patient, a kindergarden teacher, already treated with corticosteroid and antiviral agents as soon as BP was diagnosed. Six weeks later, patient didn’t recover, with House-Brackmann score stage 3. Acupuncture was perfomed at local and distance acupoints at ears, body and face. Wrist Ankle Acupuncture (WAA) L1,2; ear acupuncture at zero point; and body points were stimulated by electroacu-puncture. After acupuncture therapy, the House-Brackmann score was grade 2. Medical options for the sequelae of BP are limited. Acupuncture’s effectivity in Bell palsy patients’ should be shown with more clinical studies. Keywords: Acupuncture; Wrist Ankle Acupuncture; Bell’s Palsy; Recovery